ANALISIS YURIDIS PENGGUNAAN ALAT GLOBAL POSITIONING SYSTEM (GPS) OLEH PENGEMUDI KENDARAAN MENURUT UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Haffid Lufthi; Dessy Artina; Zainul Akmal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Global Positioning System (GPS) is a system that functions to make it easier for adriver to obtain information about his position and can perform Route Tracking and find anaddress so that it is useful for fuel and travel time destinations. The problem regarding theGlobal Positioning System (GPS) stems from the Traffic and Road Transportation Law,which drives vehicles with full concentration as stipulated in Article 106 of the Road Trafficand Transportation Law (LLAJ). This is where this article implies that the use of the GlobalPositioning System (GPS) when driving can cause accidents, so that when viewed fromArticle 106 paragraph 1 of the Traffic Law there is a lack of clarity in the rules.The conclusions that can be obtained from the results of the research are: First, theinterpretation of the law regarding "doing other activities or something that results inimpaired concentration while driving in Article 283 of Law Number 22 of 2009 with the 1945Constitution as long as it is not interpreted. satellite which is usually called the GlobalPositioning System (GPS) contained in a smartphone (smartphone) is unreasonableaccording to law and the article is still considered relevant. Second, the ideal arrangement inguaranteeing legal certainty for the use of the Global Positioning System (GPS) device is thatthe norm cannot access a complete understanding of the norms contained in Article 106paragraph (1) of Law Number 22 of 2009. This norm contains the norms of command whichobliges everyone to drive their vehicle fairly and with full concentration. In the context ofcreating and passing safety against violations of the norms in question, it is necessary to givethe threat of sanctions whose formulation is placed at the end before closing.This type of research can be classified in the type of normative legal research,which discloses laws and regulations relating to legal theories that are the object ofresearch. The approach taken is using a qualitative analysis approach by searching for datain books, journals and other scientific works related to this research. The data sources usedare primary and secondary legal materials.Keywords: GPS, Traffic, Transportation, Road Transportation.